Administration of alemtuzumab and G‐CSF to adults with relapsed or refractory acute lymphoblastic leukemia: results of a phase II study. (28th August 2013) - Gorin, Norbert‐Claude; Isnard, Françoise; Garderet, Laurent; Ikhlef, Souhila; Corm, Selim; Quesnel, Bruno; Legrand, Ollivier; Cachanado, Marine; Rousseau, Alexandra; Laporte, Jean‐Philippe
Abstract: The outlook for adults with refractory and relapsed acute lymphocytic leukemia (ALL) is poor. CD52 is expressed in most patients with ALL. Alemtuzumab is an anti‐CD52 humanized monoclonal antibody. This phase II study assessed the efficacy of alemtuzumab combined with granulocyte‐colony stimulating factor (G‐CSF) to boost antibody‐dependent cell cytotoxicity mediated by neutrophils. Twelve patients with relapsed ( n = 11) or refractory ( n = 1) ALL, including four relapses postallogeneic stem cell transplantation, were treated and monitored between October 2006 and January 2011. Patients received 1 wk of alemtuzumab every other day at increasing doses of 3, 10, and 30 mg to test tolerance and 30 mg three times a week for 12–18 infusions. If in complete remission (CR), patients received maintenance therapy for 1 wk, every 2 months. G‐CSF was administered at 5 μg/kg per day during alemtuzumab administration. The primary endpoint was disappearance of blast cells on a marrow aspirate. CD52 was expressed in all patients. Four patients reached CR. In one additional patient, clearance of blast cells was observed in peripheral blood but not in the marrow. The most frequent adverse events during course 1 of treatment were fever and chills ( n = 3), skin rash ( n = 3), and bronchospasm ( n = 2). Tumor lysis syndrome was observed at treatment initiation in one patient who reached CR. All patients progressed within a few months and all but one died. The surviving patient is still alive after relapse and a second allogeneic stem cell transplantation. This study shows that in relapse/refractory ALL, alemtuzumab with G‐CSF can produce good responses of short duration.